Peter Grasselli, ljubljanski župan 1883-1896 - Matić, Dragan (Studia Historica Slovenica, 2017)
The term of Peter Grasselli as Mayor was of great importance to the Slovenians in Carniola. The acquisition of the Ljubljana magistrate had both symbolic and far-reaching national political significance in the bitter struggle against Germanization, which in Carniola had made considerable progress in the 1970s. Peter Grasselli proved to be a patriotic politician. During his term, with the strong support of the provincial president, the provincial council and the government in Vienna, Ljubljana gradually changed from a German provincial city to the Slovenian capital.
Keywords: Grasselli, Peter; Hribar, Ivan; Ljubljana; politična zgodovina; Slovenija; župani